2019
DOI: 10.1101/809608
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ILF3 contributes to the establishment of the antiviral type I interferon program

Abstract: Upon detection of viral infections, cells activate the expression of type I interferons (IFNs) and pro-inflammatory cytokines to control viral dissemination. As part of their antiviral response, cells also trigger the translational shutoff response which prevents translation of viral mRNAs and cellular mRNAs in a non-selective manner. Intriguingly, mRNAs encoding for antiviral factors bypass this translational shutoff, suggesting the presence of additional regulatory mechanisms enabling expression of the self-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…In splicing factor analysis, ILF3 and SRSF7 are identified as a splicing factor affecting the splicing of exons. ILF3 plays a role in antiviral response by inducing the expression of interferon-stimulated genes [46]. In another computational analysis, SRSF7 is also predicted to have binding potential with SARS-CoV-2 RNA [47].…”
Section: Discussionmentioning
confidence: 99%
“…In splicing factor analysis, ILF3 and SRSF7 are identified as a splicing factor affecting the splicing of exons. ILF3 plays a role in antiviral response by inducing the expression of interferon-stimulated genes [46]. In another computational analysis, SRSF7 is also predicted to have binding potential with SARS-CoV-2 RNA [47].…”
Section: Discussionmentioning
confidence: 99%
“…In one case, A549 cells infected with Sendai virus exhibited decreased IFN upon small interfering RNA knockdown of ILF3 (28). A more recent study in HeLa cells found that NF110 enhanced translation of IFNB1 mRNA and a subset of ISGs (27). Given that the mechanisms regulating innate immune sensing and IFN production are known to be different between cell lines of immune and nonimmune origin (84), it is not particularly surprising that ILF3's function is context dependent.…”
Section: Discussionmentioning
confidence: 99%
“…We were particularly intrigued by the transcription factor ILF3, as it has been reported to negatively regulate IFN production during influenza infection in primary human bronchial epithelial cells (26). Additionally, under different experimental conditions in HeLa and A549 cells, ILF3 has been shown to promote the IFN response upon dsRNA stimulation (27,28). The gene encoding ILF3 produces two major isoforms, NF90 and NF110 (collectively named ILF3 for the purposes of this study), and both are known to act as transcriptional regulators (1113, 2931).…”
Section: Temporal Promoter and Transcriptome Analysis Predict Ilf3 As...mentioning
confidence: 99%
“…A dsRNA binding protein ILF3 was identified from (8 total:4 unique) peptides in the infected sample. This protein was shown to be important for the establishment of dsRNA-induced anti-viral signaling and to either promote or inhibit the replication of diverse viruses (97)(98)(99)(100)(101). The ILF3 gene is expressed as multiple isoforms of the two major variants of 90KDa and 110KDa proteins.…”
Section: Identification Of Novel Factors Affecting Viral Replication ...mentioning
confidence: 99%